"جريمة الامتناع عن إغاثة الملهوف، والمسؤولية المترتّبة عليها ""دراسة مقارنة بين الشريعة الإسلامية والقانون الجزائري""" - قعار, زكرياء; خلايفه, نور الدين (University of Eloued جامعة الوادي, 2020)
إن الامتناع عن تقديم المساعدة لشخص في حالة الضّرورة يعد النوع الثاني من الجرائم التي تستلزم العقوبة لتعارضها مع قيم التّعاون والتّسامح التّي تسود المجتمعات الإنسانية، لذا وقع اختيارنا على هذا الموضوع المعنون ب: (جريمة الامتناع عن إغاثة الملهوف، والمسؤولية المترتّبة عليها، دراسة مقارنة بين الشّريعة الإسلامية والقانون الجزائري)، وقد تطرّقنا فيه إلى مبحثين يتضمّن كلّ منها مطلبان، حيث اشتمل المبحث الأول على بيان لبعض تعريفات فقهاء الشريعة الإسلامية والقانون الجزائري لجريمة الامتناع، كما احتوى على بعض المصطلحات المتعلّقة بهاته الجريمة وهذا لبيان الفروقات بينها، فهذا في المطلب الأول، وأما المطلب الثاني فيتضمّن تقسيمات الفقهاء عموما لجريمة الامتناع، وفي المبحث الثاني في المطلب الأول فيه بيان للأركان الأساسية التي تقوم عليها هاته الجريمة، وأما المطلب الثاني سنتطرّق إلى أثرها على ثبوت مسؤولية الجاني، إضافةً إلى تحليلنا لبعض القضايا التّطبيقية المعروضة من طرف المحاكم التي تحكم بنصوص الشّريعة الإسلامية كالمملكة العربيّة السّعودية، والمحاكم الجزائرية التي تحكم بنصوص القانون، وفي الأخير ختمنا هاته الدّراسة بخاتمة اشتملت على أهم النّتائج والتّوصيات التّي توصّلنا إليها.Refraining from supplying aid to a person in case of necessity is considered as the second type of crime that requires punishment due to its contradiction with the values of cooperation and tolerance that prevail in human societies; therefore, this topic entitled:" The crime of refraining from providing assistance to people in urgent need and the responsibilities ensued " has been selected . It is a comparative study between the Islamic and the Algerian law. This study comprises two parts.Each one includes two sections.In the first part, the first sectionconsists of some definitions of jurisprudents and jurists of the Algerian law of the crime of refraining .It also contains some terms related to this crime in order to clarify the differences between them.Regarding the second section ,it includes the divisions,made by the jurisprudents, of the crime of refraining. In the second part, the first section is dedicated to the fundamental pillars on which this crime is based. The second section is about its effects on proving the responsibility of the perpetrator. In addition to that, it brings an analysis to some applied issues in courts applying Sharia in Saudi Arabia as well as Algerian courts applying the law. In the end , The study is concluded in a way bringing the most important findings and recommendations reached.
مذكرة ماستر تخصص شريعة وقانون
Keywords: جريمة الامتناع - إغاثة الملهوف - المسؤولية; The crime of abstinence - relief of the distressed - responsibility